Youth volunteering for disaster preparedness in Port Dickson, Negeri Sembilan, Malaysia / Mohd Ramlan Mohd Arshad, Nur Ain Athirah Mohamad Rizal and Nor Faprizalin Zamzam - Mohd Arshad, Mohd Ramlan; Mohamad Rizal, Nur Ain Athirah; Zamzam, Nor Faprizalin (Universiti Teknologi MARA, Perlis, 2022)
The increasing number of disasters in Malaysia has resulted in the increasing demand for volunteers. The need for volunteers is to ensure the disaster management system can operate well during emergency breaks. This study aimed to measure youth's volunteerism for disaster preparedness in Port Dickson, Negeri Sembilan, Malaysia. The 240 respondents for this research are youths who live in Port Dickson with a range of ages between 15-35 years old. Convenience and Purposive Sampling techniques were used with a questionnaire as the instrument. To answer the research questions, Correlation and Regression Analysis were conducted. Based on the research findings, the level of disaster preparedness among youths is at a moderate point. The other variables tested namely education, altruism, personal development, social interaction, and family volunteering show there is a significant relationship in improving the level of volunteerism among youth for disaster preparedness. The result shows that education is the most contributor to youth volunteerism for disaster preparedness. This summarizes that in ensuring a high level of youth involvement, all parties must work together to educate the youngsters on the importance of volunteering to prepare for disaster breaks. It will help to strengthen the disaster support system as the youths are well prepared for emergency times. The result of this research will benefit the policymakers, national security, disaster agencies, NGOs, and related parties in terms of developing volunteerism enthusiasm among youths in Malaysia